Waqf for education in Malaysia: historical implementation, types, and significance - Mohamad Rohana, Noor Aziera; P. Rameli, Mohd Faizal; Surtahman, Asma’ Wardah; Abdul Razak, Abdul Qayyum; Halim, Faiqah Hafidzah; Mohd Amin, Suhaida (2023)
Waqf for Education (Waqf al-Tadris) focuses on supporting educational institutions, such as schools, colleges, universities, and vocational training centres. The income generated from the waqf assets is used to fund the operational costs, scholarships, teacher salaries, infrastructure development, and educational programs of these institutions. This study aims to identify the concept and historical implementation of educational institutions based on waqf in Malaysia. The study also attempts to explain the types of waqf-based educational institutions in Malaysia. At the same time, this study also presents the reasons for the existence of such forms of waqf-based educational institutions in Malaysia. The data and information for this study were gathering from library resources. Document analysis were use in examining and interpreting written or textual materials to gain insights and understandings about a particular topic, phenomenon, or research question. This study concludes, Waqf education in Malaysia refers to the establishment and management of educational institutions and programs through the utilization of waqf funds. Waqf education plays a significant role in supporting educational initiatives and ensuring sustainable funding for educational institutions especially in Islamic-based education. Various types of waqf are established to serve different purposes and cater to the diverse needs of the community in Malaysia. Efforts should be made to raise awareness and educate the community about the importance of waqf in education. Waqf education serves as a catalyst for personal, social, and economic development, creating a positive impact on individuals, communities, and societies. It promotes educational inclusivity, fosters moral values, drives socioeconomic empowerment, and contributes to the overall well-being and progress of society